Participation in Good Governance Principles Related to Citizenship Protection Ex-Isis Indonesian Citizen - Aulia Rahman AK; Heru Susetyo; Ceruang Alang (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2024)
Citizenship is an obligation to recognize, protect, and fulfill human rights for a state governed by the Rule of Law. The government has a responsibility outlined in the principles or principles or general principles of good governance (Algemene beginselen van behoorlijk bestuur) to serve the public (public service) of the people as Indonesian citizens. The government has obligations set out in the Law—Citizenship Law to consider regarding not repatriating and revoking the Citizenship of ex-ISIS Indonesian citizens. Government policy, in this case, is fundamental because every policy that is decided must be under existing regulations and the principles of Good Governance so that the government can protect ex-ISIS Indonesian citizens in fulfilling their citizenship rights. The problem in writing this Law is how the government's participation (in this case, the application of the principles of Good Governance) in protecting Indonesian citizens of ex-ISIS and what factors cause ex-ISIS to lose their Citizenship under applicable regulations in Indonesia. This research employs a normative research approach with a literature study. The analysis technique uses descriptive qualitative analysis with primary legal materials of statutory rules, secondary legal materials of scientific books, journals, articles, and tertiary legal materials. The conclusion is that the protection of ex-ISIS under Law Number 12 of 2006 concerning Citizenship and government participation in Law Number 30 of 2014 concerning Government Administration.